(3GdeSOSI GdeKdKIs - (3GHf GQaY QGSg GdCfOdSj GdLjGfj, GHf GQaY QGSg GdCfOdSj GdLjGfj,J (B593 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aGhJ Hjf EOQGc GdCagGe hHYO agPg GdeSOSI GdeKdKI GdPi ai UOQ GdeSOSI GdJGFjI eKdgG EPG KdK GdeQjN HGdRgQI GdJKdjK gfG Cf jchf GdeQjN hgh GdLhgQ GdLGQ GdjGHS s
(3BNQgG (B:s
(3hGYde Cf GdMLQ EPG HdZ GdZGHI Sei NejQI acdeG CdbjJ ajg ef GdMLQ ZHjWG hcQQ Mdg hYbOg UGQ GcSjQkG hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs